Measuring and modelling seasonal variation of carbon dioxide and water vapour exchange of a Pinus ponderosa forest subject to soil water deficit - Law, B. E.; Williams, M.; Anthoni, P. M.; Baldocchi, D. D.; Unsworth, M. H. (Global change biology, 2000)
Summary We conducted ecosystem carbon and water vapour exchange studies in an old‐growth Pinus ponderosa forest in the Pacific North‐west region of the United States. The canopy is heterogeneous, with tall multiaged trees and an open, clumped canopy with low leaf area. Carbon assimilation can occur throughout relatively mild winters, although night frosts can temporarily halt the process and physiological factors limit its efficiency. In contrast, carbon assimilation is often limited in the ‘growing season’ by stomatal closure associated with high evaporative demand (D) and soil water deficits. All of these factors present a challenge to effectively modelling ecosystem processes. Our objective was to generate an understanding of the controls on ecosystem processes across seasonal and annual cycles from a combination of fine‐scale process modelling, ecophysiological measurements, and carbon and water vapour fluxes measured by the eddy covariance method. Flux measurements showed that 50% and 70% of the annual carbon uptake occurred outside the ‘growing season’ (defined as bud break to senescence, ∼ days 125–275) in 1996 and 1997. On a daily basis in summer, net ecosystem productivity (NEP) was low when D and soil water deficits were large. Whole ecosystem water vapour fluxes (LE) increased from spring to summer (1.0–1.9 mm d−1) as conducting leaf area increased by 30% and as evaporative demand increased, while evaporation from the soil surface became a smaller portion of total LE as soil water deficits increased. The models underestimated soil evaporation, particularly following rain. In the SPA model, varying the temperature optimum for photosynthesis seasonally resulted in overestimation of carbon uptake in winter and spring, showing that in coniferous forests, assumptions about temperature optima are clearly important. Daily estimates of soil surface CO2 flux from measurements and site meteorological data demonstrated that modelling of soil CO2 flux based on an Arrhenius‐type equation in CANPOND overestimated CO2 respired from the soil during drought and when temperatures were low.